Effect Of Arm And Core Length On Serve Receiving Accuracy And Court Defending From 2nd Position Of Premier League In Volleyball Players - Amjad Hamed Badr (Journal of Education and Sport Science, 2024)
Objectives: This study aimed to determine the contribution of arm length and torso length to serve reception accuracy and field defense accuracy from position 2 among Premier League volleyball players. Materials and Methods: This study used a descriptive survey method. The population consisted of 140 players from 10 Premier League volleyball clubs. The sample was selected purposively, involving 24 players from 8 clubs. A pilot test was also conducted with 12 players from 2 clubs. Data were collected through anthropometric measurements and volleyball skill tests, then analyzed using descriptive and correlational statistics. Results: The results showed that torso length had a significant relationship with serve reception accuracy. This finding indicates that torso length may support balance and stability during volleyball performance. However, arm length did not show a significant effect on serve reception or field defense accuracy from position 2. Conclusions: Torso length contributed to serve reception accuracy, while arm length was not a strong predictor of serve reception or field defense performance. Field defense from position 2 may be more influenced by agility, reaction speed, balance, and coordination.